ASPECTS REGARDING THE PROMOTION OF ECOTOURISM TO CONSUMERS - Mirela-Cristina VOICU (Challenges of the Knowledge Society, 2018)
The environment is a key factor for the success of the tourism industry. If we consider nature a product of the tourism industry, it is obvious that the product will no longer be purchased by consumers, if it begins to have a low quality. This is why all stakeholders of the tourism business should be aware of the importance of preserving the environment and natural resources. Hence the need to promote and stimulate ecotourism consumption. Ecotourism combines the pleasure of discovering and learning about fauna, flora, and spectacular cultural sites with educational accents, environmental, and local community benefits. Ecotourism that is properly designed and managed leads to a balance between nature conservation and the need for tourism development. Due to growing demand, the eco-tourism market is becoming more and more diverse, so for businesses operating or seeking to operate in this market the need to know the behavior of ecotourists is becoming increasingly important in order to „manipulate” more efficiently both the ecotourist and his experience. Thus, understanding the needs and attitudes of ecotourists who spend their holidays in protected areas can contribute to the development of tourism marketing strategies and plans. In this context, the following paper reveals some important aspects regarding the characteristics of ecotourists behavior together with solutions that marketers can apply to stimulate the consumption of ecotourism.